EmocioNatura: Eco-pedagogical Strategies to Know, Feel and Love Nature (Biocenosis, 2021)
This article shines the spotlight on the need to reconnect with nature from the earliest life stages, to reinforce the affective bond with it, and generate pro-environmental behaviors in the face of the current global eco-social crisis. EmocioNatura consists of a socio-educational intervention project applied in educational centers in Costa Rica. Its purpose is for participants to know, feel and love nature, through environmental education didactic strategies with a sensorial, creative, and emotional approach.
Keywords: early childhood education; environmental education; sensory development; emotion; experimental pedagogy